Pseudoaneurysm of Muscular Artery in the Thigh Following Low-Energy Trauma: A Case Report - Rosati, Luis Fernando; Rosati, Ana Paula Miranda; Rocha, Ana Luiza de Carvalho Miranda Rosati; Ribeiro, Jorge; de Oliveira, Rayane Freitas; Pimenta, Davi Couto; de Matos, Jennifer Ferreira (Brazilian Journal of Case Reports, 2025)
This report presents the case of a 38-year-old female who developed a pseudoaneurysm in the left thigh two years after a low-energy fall. Progressive thigh swelling prompted further evaluation. Initial computed tomography (CT) revealed a large vascular lesion, approximately 15 cm, but lacked definitive pseudoaneurysm characteristics. Doppler ultrasound provided diagnostic clarity, demonstrating the characteristic "yin-yang" sign indicative of bidirectional blood flow. The patient underwent successful surgical resection, with an aspirative drain removed on the tenth postoperative day. This case emphasizes the diagnostic complexities of pseudoaneurysms, particularly in delayed trauma presentations, and underscores the vital role of Doppler ultrasound in identifying vascular flow dynamics. Additionally, it highlights the necessity of a multidisciplinary approach in managing complex vascular lesions, combining diagnostic precision and tailored therapeutic strategies.